Life expectancy and disparity: an international comparison of life table data - Vaupel, James W (BMJ Group, 2011)
OBJECTIVES: To determine the contribution of progress in averting premature deaths to the increase in life expectancy and the decline in lifespan variation. DESIGN: International comparison of national life table data from the Human Mortality Database. SETTING: 40 developed countries and regions, 1840–2009. POPULATION: Men and women of all ages. MAIN OUTCOME MEASURE: We use two summary measures of mortality: life expectancy and life disparity. Life disparity is a measure of how much lifespans differ among individuals. We define a death as premature if postponing it to a later age would decrease life disparity. RESULTS: In 89 of the 170 years from 1840 to 2009, the country with the highest male life expectancy also had the lowest male life disparity. This was true in 86 years for female life expectancy and disparity. In all years, the top several life expectancy leaders were also the top life disparity leaders. Although only 38% of deaths were premature, fully 84% of the increase in life expectancy resulted from averting premature deaths. The reduction in life disparity resulted from reductions in early-life disparity, that is, disparity caused by premature deaths; late-life disparity levels remained roughly constant. CONCLUSIONS: The countries that have been the most successful in averting premature deaths have consistently been the life expectancy leaders. Greater longevity and greater equality of individuals' lifespans are not incompatible goals. Countries can achieve both by reducing premature deaths.